Preview-Publication-April 23 RESPONSIBLE LEADERSHIP AND ACCOUNTABILITY CHALLENGE IN NIGERIA’S PUBLIC ADMINISTRATION AND SUSTAINABLE DEVELOPMENT: A GLOCALISED PERSPECTIVE. - Stephen Chinedu Chioke (Innovative Issues and Approaches in Social Sciences, 2023)
While considering the idea of glocalisation, responsible leadership as a matter of importance must be characterized by innovation and social engineering. Also, Nigeria’s leadership and public accountability questions, problems and allied negativities must be scientifically understood in order to attain sustainable development. The reason for this is that Nigeria in recent times is fraught with divergent leadership challenges which have made the attainment of sustainable development overtly impossible. Therefore, with heavy emphasis on qualitative research approach, the study sets out to interrogate prerequisites for responsible leadership and accountability in Nigeria’s public administration and sustainable development; implications for responsible leadership and accountability challenge in Nigeria’s public administration and sustainable development. The study revealed inter alia that responsible leadership and accountability challenge encouraged loss of money in Nigeria and so on. It therefore concluded that, responsible leadership accountability challenge in the Nigeria’s public administration grossly affects sustainable development. The study recommended periodic briefing of the electorate with regard to the functionalities of government and its agencies as a way forward.